2019
DOI: 10.5507/bp.2019.008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mode of anaesthesia for caesarean delivery on neonatal Apgar scores in the Czech Republic and Slovakia: secondary analysis of the results of an international survey in 2015

Abstract: OBAAMA-INT Study Group Aims. The purpose of this international survey was to describe the impact of current practices and techniques of caesarean section on the neonatal Apgar score in the Czech Republic (CZE) and Slovakia (SVK). Methods. All Czech and Slovak departments that provide obstetric anaesthesia were invited to participate in a onemonth (November 2015) prospective study that monitored in details all peripartum anaesthetic practices, delivered by anaesthesiologists. Participating centers recorded all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Hence, an Apgar score of nine and below was considered as bad outcome in our setting. In the study conducted by Harazim et al [6], outcomes of newborns born from mothers who underwent regional anesthesia for CS had significantly better Apgar scores compared to those who underwent general anesthesia. Our study did not compare spinal anesthesia with general anesthesia; this is a gap for future research in Eritrea.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Hence, an Apgar score of nine and below was considered as bad outcome in our setting. In the study conducted by Harazim et al [6], outcomes of newborns born from mothers who underwent regional anesthesia for CS had significantly better Apgar scores compared to those who underwent general anesthesia. Our study did not compare spinal anesthesia with general anesthesia; this is a gap for future research in Eritrea.…”
Section: Discussionmentioning
confidence: 94%
“…Apgar scores recorded by an experienced neonatologist for every newborn are part of good clinical practice. In an international survey by Harazim et al [6], an experienced neonatologist was recording the Apgar score; thus a cut-off of seven and below was considered as poor outcome. In our case Apgar score below seven is considered as life-threatening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some literatures showed no difference in neonatal outcomes between general and regional anesthesia for caesarean section when only out-of-risk newborns were analyzed. 18 But for the very preterm infants (27-32 weeks), multivariate analysis showed that neuraxial block was associated with an increased risk of neonatal mortality compared to GA, disregarding the gestational age, characteristics of pregnancy, delivery and neonates. 19 In conclusion, pregnancy with internal and sur-…”
Section: Maternal and Fetal Outcomesmentioning
confidence: 96%
“…Harazim in the Czech Republic and Slovakia published in 2015, which revealed no significant difference in the APGAR score at 10 minutes in either the general anesthesia group or spinal anesthesia. [13] 5 Conclusions…”
Section: Table 1 Frequency Distribution Of Types Of Anesthesiamentioning
confidence: 99%